2016
DOI: 10.1021/acs.analchem.6b02501
|View full text |Cite
|
Sign up to set email alerts
|

Signal-Switchable Electrochemiluminescence System Coupled with Target Recycling Amplification Strategy for Sensitive Mercury Ion and Mucin 1 Assay

Abstract: In the present work, we first found that mercury ion (Hg(2+)) has an efficient quenching effect on the electrochemiluminescence (ECL) of N-(aminobutyl)-N-(ethylisoluminol) (ABEI). Since we were inspired by this discovery, an aptamer-based ECL sensor was fabricated based on a Hg(2+) triggered signal switch coupled with an exonuclease I (Exo I)-stimulated target recycling amplification strategy for ultrasensitive determination of Hg(2+) and mucin 1 (MUC1). Concretely, the ECL intensity of ABEI-functionalized sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…[19][20][21] The thymine (T) base of oligonucleotide specic binding with Hg 2+ to form "T-Hg 2+ -T" complex, and since it was reported, 22 many sensors for detection of Hg 2+ have been developed based on it. 23,24 Liu developed a Hg 2+ detection method with a detection limit of 0.5 nM by using Hg 2+ specic probe (18T) and the intercalation dye SYBR Green I. 25 In order to expand the application of detection methods, nanomaterials have been employed to construct sensitive sensors for Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] The thymine (T) base of oligonucleotide specic binding with Hg 2+ to form "T-Hg 2+ -T" complex, and since it was reported, 22 many sensors for detection of Hg 2+ have been developed based on it. 23,24 Liu developed a Hg 2+ detection method with a detection limit of 0.5 nM by using Hg 2+ specic probe (18T) and the intercalation dye SYBR Green I. 25 In order to expand the application of detection methods, nanomaterials have been employed to construct sensitive sensors for Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al introduced the amplification of RCA to report a highly sensitive ECL sensor for Hg 2+ . Besides the polymerase, Jiang et al also used exonuclease I to develop ECL sensor for Hg 2+ . Embedded ECL reagents owning high affinity with dsDNA, Ru(phen) 3 2+ and Ru‐dppz, have been also employed to develop label‐free ECL sensors for Hg 2+ .…”
Section: The Application Of Ecl Fna‐based Sensors In Food Contaminantsmentioning
confidence: 99%
“…Therefore, reliable methods for detection of Hg 2+ have become increasingly important. In recent years, ECL has been widely used as one of the main method of detecting Hg 2+ owing to its excellent performance in terms of sensitivity, stability and so on ,. In addition, a large number of studies have shown that the design of the specific binding of T to Hg 2+ is the basis for ensuring good selectivity of the sensor ,.…”
Section: Introductionmentioning
confidence: 99%